The phonological changes of Surinamese Javanese: A language contact perspective - Rofiq, Zainur (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
This article aims at discussing the phonological variation of Surinamese Javanese in language contact with Dutch and Sranantongo. It has been conducted to scrutinize the specific differences regarding the phonology in Surinamese Javanese in comparison to its counterpart in Indonesia. The study involved the recordings of 16 native speakers of Surinamese Javanese and the recordings of 7 native speakers of Indonesian Javanese, all narrating a picture-story in Javanese Ngoko. The results disclose five phonological alternations: palatal plosive to voiceless and voiced alveolo-palatal affricates, vowel shift from central close-mid to front close, nasal-stop combinations, retroflex to non-retroflex plosive changes, and the change of alveolar nasal to velar nasal in suffixes. These suggest influences from Dutch and Sranan as well as independent developments in Surinamese Javanese. The general finding of the study is that language contact in the multilingual environment of Suriname significantly impacted the phonology of Surinamese Javanese, giving it a dynamic nature of language change under these circumstances.